HUBUNGAN ANTARA PAPARAN TIMBAL (Pb) DENGAN LAJU ENDAP DARAH PADA PEKERJA BAGIAN PENGECATAN INDUSTRI KAROSERI DI SEMARANG - Setyoningsih, Oktavia Suci; Setiani, Onny; Darundiati, Yusniar Hanani (Fakultas Kesehatan Masyarakat, 2016)
The workers painting in karoseri industry, risked to exposure lead (Pb) that contained inside the paint. Lead (Pb) was cause the deficiency of the enzyme G-6PD and inhibit the enzyme pyrimidine-5'-nukleotidase. This caused decreased erythrocyte life span and increased the fragility of erythrocyte membranes, resulted in the number of erythrocytes decreased. It greatly affected the erythrocyte sedimentation rate of the workers. This study aimed to determine the correlation between exposure to lead (Pb) and erythrocyte sedimentation rate on the workers painting in karoseri industry in Semarang. This type of research was an analytic observational study with cross sectional approach. The population in this study was the workers painting in karoseri industry in Semarang as many as 53 workers. Samples used as many as 34 workers used purposive sampling technique. The result of the study by Spearman rank correlation test showed that there was no correlation between the levels of lead in the blood and erythrocyte sedimentation rate in 1 hour (p-value = 0.534) even to the erythrocyte sedimentation rate in 2 hours (p-value = 0.436). The conclusion of this study was there was no correlation between the levels of lead in the blood and erythrocyte sedimentation rate in 1 hour even to the erythrocyte sedimentation rate in 2 hours. The suggestions in this study should the company develop policies to reduced the risk of lead exposure to workers and struggled to cope with high levels of lead in the blood of workers.